Investigation into the catalytic activity of microporous and mesoporous catalysts in the pyrolysis of waste polyethylene and polypropylene mixture - Li, Kaixin (2022)
Catalytic pyrolysis behavior of synthesized microporous catalysts (conventional Zeolite Socony Mobil–5 (C-ZSM-5), highly uniform nanocrystalline ZSM-5 (HUN-ZSM-5) and β-zeolite), Mesoporous catalysts (highly hydrothermally stable Al-MCM-41 with accessible void defects (Al-MCM-41(hhs)), Kanemite-derived folded silica (KFS-16B) and well-ordered Al-SBA-15 (Al-SBA-15(wo)) were studied with waste polyethylene (PE) and polypropylene (PP) mixture which are the main constituents in municipal solid waste. All the catalysts were characterized by Brunauer-Emmett-Teller (BET), X-ray powder diffraction (XRD), and NH3-temperature programmed desorption (TPD). The results demonstrated that microporous catalysts exhibited high yields of gas products and high selectivity for aromatics and alkene, whereas the mesoporous catalysts showed high yields of liquid products with considerable amounts of aliphatic compounds. The differences between the microporous and mesoporous catalysts could be attributed to their characteristic acidic and textural properties. A significant amount of C2–C4 gases were produced from both types of catalysts. The composition of the liquid and gas products from catalytic pyrolysis is similar to petroleum-derived fuels. In other words, products of catalytic pyrolysis of plastic waste can be potential alternatives to the petroleum-derived fuels.